Giant plunging ranula: a case report - Kim, Seong-Ha (Korean Academy of Oral and Maxillofacial Radiology, 2013)
A ranula is a bluish, transparent, and thin-walled swelling in the floor of the mouth. They originate from the extravasation and subsequent accumulation of saliva from the sublingual gland. Ranulas are usually limited to the sublingual space but they sometimes extend to the submandibular space and parapharyngeal space, which is defined as a plunging ranula. A 21-year-old woman presented with a complaint of a large swelling in the left submandibular region. On contrast-enhanced CT images, it dissected across the midline, and extended to the parapharyngeal space posteriorly and to the submandibular space inferiorly. Several septa and a fluid-fluid level within the lesion were also demonstrated. We diagnosed this lesion as a ranula rather than cystic hygroma due to the location of its center and its sublingual tail sign. As plunging ranula and cystic hygroma are managed with different surgical approaches, it is important to differentiate them radiologically.